Development of a Psychometric Test: A Care Risk Scale for Homebound Older People With Dementia - Dong, Xiaoxin; Zhao, Lingbo; Kong, Xianbo; Xu, Ting; Sun, Tongda (Frontiers in Psychology, 2022)
Background: Homebound older people with dementia (OPWD) face a series of care risks due to disease characteristics, care issues, and the family environment. However, China lacks a quantitative assessment tool for care risk. Thus, we attempted to develop a care risk scale for homebound OPWD. Methods: A care risk scale, with initially 18 items, was designed based on a systematic literature review, expert consultation, and a pilot study with 20 OPWD. The initial scale was validated among 1045 homebound OPWD in Ningbo, China from November 1, 2020 to July 30, 2021. After removing three items that lacked discrimination power, the reliability and validity of the remaining 15itemswas evaluated. Results: The final scale consisted of 15 items assessed on a 5-point Likert scale that loaded on to three different factors, including dementia symptoms (four items), family support (four items), and home environment (seven items). These three factors explained 77.77% of the cumulative variance among the objects of the psychometric test. The overall Cronbach’s alpha for the final scale was 0.907. The correlation coefficients in the item-to-total analysis ranged from 0.511–0.662. Conclusion: The validation analysis indicated satisfactory reliability and validity of the 15-item scale for assessing care risk of homebound OPWD. This scale can help long-term care professionals and family caregivers identify care risks and help them take targeted measures to enhance safety of care for OPWD.